A case study objectively assessing female physical activity levels within the National Curriculum for Physical Education. (May 2015) - Hobbs, Matthew; Daly-Smith, Andrew; Morley, David; McKenna, James
The purpose of this study was to assess the impact of the National Curriculum for Physical Education (NCPE) lesson themes and contexts on the profile of moderate-to-vigorous physical activity (MVPA). Fifteen, Year 9 Physical Education (PE) lessons were assessed within the lesson themes of Outwitting Opponents (OO) (delivered through field hockey and netball) and Accurate Replication (AR) (delivered through gymnastics) using the System for Observing the Teaching of Games in Physical Education. Accelerometry identified MVPA within PE lessons (Actigraph-GTM1, 10-second epoch, MVPA ≥2296 counts/min). Among 112 females MVPA averaged 20.8% of available learning time. Significantly more MVPA was facilitated during OO than AR (22.7 vs. 15.9%, p < 0.001, d = 0.88). Within both lesson themes, warm-up was the most active lesson context while pre- and post-lesson general management were the least active. Contrary to expectations, neither small-sided nor modified games, versus full-sided games, increased MVPA within OO. During AR technical and applied-skill practice resulted in low MVPA. Objective evidence has justified concerns about female adolescent MVPA within PE. At current levels an additional 17.5 minutes of MVPA per 60 minute PE lesson would be needed to meet the minimum 50% guideline.